Comparison of neuromuscular fatigue in powerlifting Paralympics in different training methods - Getirana-Mota, M.; Aidar, F. J.; Neto, F. R.; Santos, T. P.; de Almeida-Neto, P. F.; Cabral, B. G. A. T.; Vieira-Souza, L. M.; Garrido, N. D.; Reis, V. M.; Souza, R. F. (Sports Medicine International Open, 2024)
Mean propulsive velocity (MPV) has been associated with neuromuscular fatigue; however, its suitability for strength training in Paralympic powerlifting (PP) remains uncertain. The objective of this work was to evaluate the MPV in two training methods (traditional-TRAD and eccentric-ECC). Eleven PP athletes were evaluated pre, during the intervention and post intervention at a load of 80% of the 1RM for TRAD and 110%-80% of 1 RM for ECC. The results demonstrated that there was no significant neuromuscular fatigue for the TRAD (~5% performance loss), as well as no significant decline in MPV during the intervention. For the ECC, there is a significant reduction in MPV before and after training (~12% loss of performance). A difference between TRAD and ECC after the intervention was also identified (0.87 m/s±0.22, 95% CI 0.72-1.02 vs. 0.72±0.20, 95% CI 0.59-0.86 p=0.042, F(3.30)=10.190, ?2p=0.505 - very high effect). During the intervention for ECC, no significant decline in MPV was observed. The results of this study suggest that the mechanical indices of MPV do not seem to be effective indicators of neuromuscular fatigue in the sample studied or in the context of this specific training regime, being more indicated as a control of training volume.